Fondos mutuos de inversión en valores e impuesto a la renta - Polo Chiroque, Roberto Edward (2013)
Are mutual funds in securities and income taxes a suitable alternative for investment? Has the attempt to simplify the system of income taxes had an adverse impact on taxpayers?Throughout the following article, the author will answer the questions noted above.Therefore, he stresses the importance of protecting the taxpayers, so that they will not be affected by the tax regime. He also notes the necessity of this to happen in order forthe mutual funds to stay as a ideal vehicle for investment.